Muslim Americans it's my country too - Ruhi Hamid; Bestall, Clifford; British Broadcasting Corporation ([United Kingdom] : BBC Worldwide, 2003)
Learn about the diversity of Muslims in American and the Muslim-American experience today. In order to challenge the misrepresentation of Muslims in America, this video examines the everyday lives of a Muslim American in a post 9-11 world
Title from cover
Executive producer, Angus Macqueen ; editor, Karen O'Connor ; film editor, Ashley Smith ; music, Courtesy of Junoon
Keywords: Muslims -- United States -- Public opinion; Islam -- United States; Muslims -- United States -- Attitudes; Terrorism -- Religious aspects -- Islam; September 11 Terrorist Attacks, 2001 -- Influence; United States -- Religion -- Public opinion